The Protestant Episcopal church in the city of Manila, Philippine Islands from 1898-1918 : an institutional history. - Norbeck, Mark Douglas ([Texas] : The University of Texas at El Paso, 1992)
Thesis (M.A.) - The University of Texas at El Paso